2016
DOI: 10.11114/afa.v2i2.1403
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Financial Performance, Capital Structure and Macroeconomic Factors on Firm’s Value – Evidence from Textile Companies at Indonesia Stock Exchange

Abstract: This study aims to investigate how financial performance, capital structure and macroeconomic factors may influence a firm's value in Indonesia textile industry. This research is exploratory in nature involving 20 textile companies listed in Indonesia Stock Exchange (IDX). Using panel data regression, the results show that financial performance, capital structure, inflation and exchange rate are contributory factors that influence firm's value. The better the financial performance of a company, the higher its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…According to Prihadi (2013: 192) the higher the ratio means the worse the condition of the solvency. exchange rate has no significant effect on PBV, whereas Jubaedah and Hadi (2016) stated that the exchange rate has a positive effect on PBV. Changes in exchange rates can cause changes in the price of goods, especially imported goods.…”
Section: Ho Rejected F Count> F Table (Effect) or If The Value Of F Count> From F Table The Independent Variables Simultaneously Influencmentioning
confidence: 99%
“…According to Prihadi (2013: 192) the higher the ratio means the worse the condition of the solvency. exchange rate has no significant effect on PBV, whereas Jubaedah and Hadi (2016) stated that the exchange rate has a positive effect on PBV. Changes in exchange rates can cause changes in the price of goods, especially imported goods.…”
Section: Ho Rejected F Count> F Table (Effect) or If The Value Of F Count> From F Table The Independent Variables Simultaneously Influencmentioning
confidence: 99%
“…While the result of the research conducted by (Ifeanyi and Chukwuma, 2016) indicated that the relationship between inflation and profitability had a non-significant negative effect on firm value. But according to (Al-Sharkas, 2016), and (Jubaedah et al, 2016), stated that inflation has a positive and significant effect on firm value.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the agents, as managers of companies, have interests or expectations that they will get a bonus or reward for their performance in managing the company. Agency theory describes that the agency relationship of a company is a collection of contracts (nexus of contracts) between the owners of economic resources (principal), and managers (agents) who take care of the use and control of these resources ( Jensen & Meckling, 1976). A conflict resides in that agency theory predicts self-interest as the role basis for economics (Riahi-Belkaoui, 2002).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%